Loudness–Duration Tradeoff in Ultrasonic Courtship Songs of Moths - Nakano, Ryo; Nagamine, Keisuke (Frontiers in Ecology and Evolution, 2019)
Moths have evolved auditory channels under predation pressure from insectivorous bats that emit ultrasonic pulses for capturing prey, including moths. Tympanate moths perform evasive behavior in response to echolocation calls of bats, but they also utilize ultrasonic signals mostly generated by males close to an intended female mate in the context of courtship. Unlike calling songs used to advertise the presence and sexual attractiveness of the signaler, courtship songs need not always be acoustically conspicuous. Male courtship songs are predominantly soft but sufficient for detection by a nearby potential mate. Quiet courtship songs are thought to effectively avoid being eavesdropped by gleaning bats, acoustic parasitoids, and conspecific competitors, i.e., rival males. However, males of some moth species generate loud courtship songs. In the present study, the duration of courtship song, in addition to the sound level of the song was predicted to affect the likelihood of being perceived by eavesdroppers. Loud and lengthy courtship songs, which are easily exploited by eavesdroppers, would be expected to rarely evolve, because a female receiver close to a male emitting a conspicuous song would also be exposed to strong predation pressure. This study explored the relationship between the peak sound level and the duration of single song bouts in 26 moth species from the following families: Noctuidae, Erebidae, Crambidae, Pyralidae, and Geometridae. The softest and loudest songs with mean peak sound levels of 64 and 129dB peSPL had mean durations of 1900 and 312 ms, respectively, whereas the shortest and longest songs with mean durations of 110 and 8839 ms had mean peak sound levels of 102 and 74 dB peSPL, respectively. Thus, the peak sound level and duration of courtship song exhibited a significant negative relationship. Although the energetic cost of producing song and the size of the sound-producing organ might also affect the relationship, the data support the conclusion that acoustic moths have adaptively evolved ultrasonic courtship songs with properties between “soft-and-long” and “loud-and-short” to avoid eavesdroppers.